2012
DOI: 10.1371/journal.pone.0047798
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Human Skin Commensal Bacteria as a Reflection of UV Radiation: UV-B Decreases Porphyrin Production

Abstract: Recent global radiation fears reflect the urgent need for a new modality that can simply determine if people are in a radiation risk of developing cancer and other illnesses. Ultraviolet (UV) radiation has been thought to be the major risk factor for most skin cancers. Although various biomarkers derived from the responses of human cells have been revealed, detection of these biomarkers is cumbersome, probably requires taking live human tissues, and varies significantly depending on human immune status. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 53 publications
(55 reference statements)
0
28
0
2
Order By: Relevance
“…Currently, it is not fully clear whether there is any correlation between P. acnes strains and their distribution in the human body. Results from our laboratory have revealed that exposure of P. acnes to ultraviolet (UV) decreased the production of porphyrins in the human facial bacteria containing different strains of P. acnes and other skin bacteria [26]. Besides P. acnes , other skin resident bacteria (e.g.…”
Section: Medical Application Of Porphyrinsmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, it is not fully clear whether there is any correlation between P. acnes strains and their distribution in the human body. Results from our laboratory have revealed that exposure of P. acnes to ultraviolet (UV) decreased the production of porphyrins in the human facial bacteria containing different strains of P. acnes and other skin bacteria [26]. Besides P. acnes , other skin resident bacteria (e.g.…”
Section: Medical Application Of Porphyrinsmentioning
confidence: 99%
“…Consequently, there is a linear relationship between the decrease in the height of the Soret band and the increase of X-irradiation dose [33]. Results in our recent publication have demonstrated that the production of porphyrins in P. acnes was significantly reduced with increasing doses of gamma radiation and UV-B [26]. The porphyrin reduction was detectable in both P. acnes and human skin bacterial isolates.…”
Section: Medical Application Of Porphyrinsmentioning
confidence: 99%
See 3 more Smart Citations